(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine the performance of the Environmental Service in waste management in Gowa Regency. This study used descriptive qualitative research methods. The informants in the study were 13 people. The data collection technique were interview, observation, and documentation. The results showed that the productivity of the performance had not been maximized because the target for reducing waste had not been met, the failure to achieve Adipura, and the schedule for disposing of waste was not disciplined. The quality of service was quite good, seen from the discipline and friendliness of the officers, but there was a need for additional heavy equipment, garbage containers and TPA improvements. Responsiveness was good, due to the provision of a report website and responsiveness to solid waste complaints. Responsibility was very good, it could be seen that employees and officers carried out their duties and functions according to the SOP. Accountability was quite good, such as the establishment of a Waste Bank UPT and control landfill standards at the TPA, but lacks transparency in general solid waste data to the public. Keywords: environmental service, performance, waste management